2015
DOI: 10.1021/acs.molpharmaceut.5b00364
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous DNA Loading into Extracellular Vesicles via Electroporation is Size-Dependent and Enables Limited Gene Delivery

Abstract: Extracellular vesicles (EVs) hold immense promise for utilization as biotherapeutics and drug delivery vehicles due to their nature as biological nanoparticles that facilitate intercellular molecular transport. Specifically, EVs have been identified as natural carriers of nucleic acids, sparking interest in their use for gene therapy and RNA interference applications. So far, small RNAs (siRNA and miRNA) have been successfully loaded into EVs for a variety of delivery applications, but the potential use of EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
262
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(282 citation statements)
references
References 47 publications
2
262
2
Order By: Relevance
“…HEK293T EVs were used as they contain minimal intrinsic biological cargos compared to EVs generated by other cells. 5 As shown in Western blots (Fig. S1a), HEK293T isolated EVs showed negative staining for several common integrin markers as seen on EVs for cancerous origins, 6, 7 with only positive staining for TSG101.…”
Section: Design and Construction Of Arrow-shaped Rna Nanostructuresmentioning
confidence: 80%
“…HEK293T EVs were used as they contain minimal intrinsic biological cargos compared to EVs generated by other cells. 5 As shown in Western blots (Fig. S1a), HEK293T isolated EVs showed negative staining for several common integrin markers as seen on EVs for cancerous origins, 6, 7 with only positive staining for TSG101.…”
Section: Design and Construction Of Arrow-shaped Rna Nanostructuresmentioning
confidence: 80%
“…Following this pioneering report, other research groups have shown comparable results for loading siRNA and even DNA strands up to a 1000 bp into EVs [164][165][166][167][168]. Besides nucleic acids, 5 nm superparamagnetic iron oxide particles and large proteins have been loaded in purified EVs using EP (table 2).…”
Section: Loading Evs With a Therapeutic Cargomentioning
confidence: 93%
“…Since the publication of this report, several groups have tried to prevent this aggregate formation through the use of chelating agents (e.g. EDTA) [166] or membrane stabilizers (e.g. trehalose) [170,171].…”
Section: Loading Evs With a Therapeutic Cargomentioning
confidence: 99%
“…Mounting evidence suggests that extracellular vesicles (EV), particularly exosomes, play a crucial role in the transfer of RNA molecules between cells as part of cell communication processes. Different encapsulation approaches have been explored for loading exosomes with DNA or siRNA molecules [47,48]. Thus, exosomes represent interesting natural carriers potentially exploitable for the delivery of RNAi to a variety of cell types and tissues, including cartilage.…”
Section: Non-viral Methods Delivering Rnai For Chondrogenesismentioning
confidence: 99%